Properties of the Rainbow multi-variant algorithm and its ability to resist various crypto-analysis methods and attack by outside channels - Harmash , D.V. (Radiotekhnika, 2021)
This work presents the analysis of the essence and possibilities of protection of the Rainbow post-quantum cryptographic algorithm. The main properties of the Rainbow algorithm and the general essence of cryptographic encryption and electronic signature algorithms based on multivariate quadratic transformations are determined. The main provisions regarding the protocols are given. Analyses are given regarding the ability to protect the algorithm against various attacks. The vulnerability of the algorithm to attack by third-party channels is investigated. The general provisions of the algorithm are considered. The algorithm is presented and considered from a mathematical point of view, as well as the mathematical essence of cryptographic algorithms for encryption and electronic signature based on multivariate quadratic transformations. The application of various methods of cryptanalysis against cryptographic algorithm based on multivariate quadratic Rainbow transformations is studied. The method of decreasing rank against the Rainbow algorithm is analyzed. The method of cryptanalysis by attacking the Oil-Vinegar scheme and the method of cryptanalysis "minranku method" are investigated. The attack is studied using a multilayer structure.